Matching Schur complement approximations for certain saddle-point systems - Pearson, JW; Wathen, AJ (Springer, 2018)
The solution of many practical problems described by mathematical models requires approximation methods that give rise to linear(ized) systems of equations, solving which will determine the desired approximation. This short contribution describes a particularly effective solution approach for a certain class of so-called saddle-point linear systems which arises in different contexts.